Hubungan Severe Early Childhood Caries (S-ECC) dengan Status Gizi Anak Usia 36-71 Bulan di Paud Kota Bukittinggi - Sherly Elsya Noviani; Arymbi Pujiastuty; Denas Symod (Faculty of Dentistry Universitas Andalas, 2022)
Background: Children with severe early childhood caries (s-ecc) will experience pain and difficulty chewing. S-ecc causes a deficiency in dietary intake and may become malnourished. Purpose: this study was aimed to know the relationship between severe early childhood caries (s-ecc) with nutritional status of chilldren at the age of 36-71 months in PAUD of Puskesmas Mandiangin, Mandiangin Koto Selayan district, Bukittinggi City. Method: obsevational analytics with cross sectional approach. The sample size was 56 children aged 36-71 months with def-t criteria ≥ 4 and selected by consecutive sampling method. S-ECC was measured using pufa index and nutritional status was measured using IMT / U. Results: the overall mean def-t children with s-ecc 7.77%. Children with positive pufa were 66.1% and those with 48.2% malnutrition status. As many as 62.2% of children with (s-ecc) positive pufa have malnutrition status. The result of statistical test using Chi-Square obtained p value = 0,008. Conclusion: There is a significant relationship between severe early childhood caries (s-ecc) with nutritional status and children with positive pufa are more at risk of malnutrition status.